YIELD, YIELD DYNAMICS AND NUTRITIONAL QUALITY OF GRASS-LEGUME MIXED PASTURE - Z. K. Tessema; B. S. Feleke (Journal of Animal and Plant Sciences, 2018)
The shortage of quality feed is a major constraint affecting livestock production in eastern parts of Ethiopia. However, the development of grass-legume mixed pasture is an alternative strategy to improve feed resources availability both in quantity and quality since forage quality and seasonal distribution of dry matter (DM) production of grass-legume mixed sward is higher compared to those grasses or forage legumes grown in pure-stands. Therefore, we studied the DM yield, competition function and chemical composition of grass-legume mixtures in a randomized complete block design with 3 replications during 2008 and 2009 cropping seasons. Chloris gayana, Panicum coloratum, Melilotus alba and Medicago sativa were planted as pure-stand and in mixtures using 50:50, 67:33, 33:67, 75:25 and 25:75 seed rate proportions of grasses and legumes, respectively. C. gayana mixed with M. alba at seed rate of 50:50 and 33:67 had a higher DM yield [27 and 26 t ha-1, respectively] than other mixtures and pure-stands. The relative total yields of all grass/legume mixtures were greater than unity, indicating that the DM yields of the mixtures were higher than those of the pure-stands. Pure-stand legumes and their mixtures with grasses had a higher crude protein contentsthan pure-stand grasses, whereas pure-stand grasses had a higher fiber fraction contents compared to pure-stand legumes and their mixture with grasses. To alleviate the feed shortage, C. gayana mixed with M. alba at seed rates of 50:50 and 33:67 can be introduced under smallholder livestock production conditions in eastern parts of Ethiopia.
Keywords: crude protein; feed shortage; fiber fraction; mixed farming; nutritive value